Hyperthermic intraperitoneal chemotherapy (HIPEC) as another treatment modality for desmoplastic round cell tumour patients: first paediatric experience from UK. Issue 1 (28th January 2021) - Sjoberg Bexelius, Tomas; Chisholm, Julia C; Okoye, Bruce; Cecil, Tom; Angelini, Paola; Dayal, Sanjeev
Abstract : We present the first young paediatric patient with desmoplastic small round cell tumour (DSRCT) treated in UK with hyperthermic intraperitoneal chemotherapy (HIPEC). A 7-year-old girl was diagnosed with abdominal DSRCT with peritoneal and liver metastases. After six cycles of chemotherapy she obtained a partial response, including almost complete resolution of the two liver metastases. It was decided to pursue cytoreductive surgery (CRS) combined with HIPEC, a procedure commonly performed in adults, but seldom in a child. The surgery was macroscopically complete and the HIPEC uncomplicated. She continued treatment without delays, including whole abdomino-pelvic radiotherapy and maintenance chemotherapy (cyclophosphamide/vinorelbine for 12 months). She is currently in complete remission 4 months after end of treatment and 26 months after diagnosis. HIPEC was made possible by successful collaboration between multiple teams. CRS-HIPEC proved to be safe and feasible and could be offered to other children with diagnoses of peritoneal malignancies across the UK.